The Influence Of Job Engagement, Job Placement, and Job Training On The Job Satisfaction Of PT Employees Grand Racing Yogyakarta - Prayekti Prayekti; F Veri Anggara; Epsilandri Septyarini (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Employees are the main capital for every company, so employees must continue to be managed well to remain productive in doing their work. The purpose of this research is to determine the effect of work involvement, work placement, and job training on job satisfaction of PT. Grand Racing Yogyakarta employees. This is a quantitative research. The sampling technique in this research is total sampling with 44 respondents. The data collection technique in this research uses a questionnaire. The quality of the instrument is tested through validity and reliability tests. Data analysis uses multiple linear regression with t test, f test, and R2. The research results show that the significance value of the variables work involvement, work placement, and work training is < α = 0.05, which means that these three variables have a positive and significant effect on job satisfaction.